2003
DOI: 10.1046/j.1472-8206.2003.00194.x
|View full text |Cite
|
Sign up to set email alerts
|

Short‐ and long‐term effects of treatment of chronic hepatitis B and delta virus by IFN

Abstract: Chronic hepatitis B virus (HBV) infection is a common infectious disease in the world. Two percent of the patients with chronic HBV infection will develop cirrhosis each year, and will die prematurely from cirrhosis or hepatocellular carcinoma. So far interferon alfa and lamivudine are the only effective drugs. Interferon alfa can be used at the dosage of 9-10 million units thrice a week for 4-6 months either intramuscularly or subcutaneously for standard treatment. Interferon provides sustained response in 1/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…On the other hand, some studies found that the efficacy of IFN on inducing hepatitis Be antigen (HBeAg) seroconversion is not so good [ 28 ] and the sustained virologic response rate was only 25 % [ 29 ]. But, the main effects of interferon are antiviral, immune regulation, and antiproliferative agents rather than the integration of HBV gene inhibitors [ 30 ]. Interferon treatment improves liver fibrosis and liver function by reducing active hepatitis [ 31 ], and it can improve overall survival by reducing the severity of the recurrence of the tumor, so it is suitable for secondary therapeutic ablation or resection [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some studies found that the efficacy of IFN on inducing hepatitis Be antigen (HBeAg) seroconversion is not so good [ 28 ] and the sustained virologic response rate was only 25 % [ 29 ]. But, the main effects of interferon are antiviral, immune regulation, and antiproliferative agents rather than the integration of HBV gene inhibitors [ 30 ]. Interferon treatment improves liver fibrosis and liver function by reducing active hepatitis [ 31 ], and it can improve overall survival by reducing the severity of the recurrence of the tumor, so it is suitable for secondary therapeutic ablation or resection [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers have found that the efficacy of IFN on inducing Hepatitis Be Antigen (HBeAg) seroconversion is far from satisfactory [25], but we should realize that IFN acted mainly as an antiviral, immunomodulatory and antiproliferative agent and not as an inhibitor of the integration of HBV DNA [26]. IFN therapy improves overall survival through relieving active hepatitis, improving hepatic fibrosis and liver function [27] as well as decreasing the severity of a recurrent tumor and thus be amenable to secondary curative ablation or resection [28].…”
Section: Discussionmentioning
confidence: 99%
“…Four, most Asian patients with CHB were probably infected by mother‐to‐child transmission, and longer duration of infection may have permitted integration of HBV DNA into the host genome: The mechanism of carcinogenesis involves many factors that are particularly complex in patients with chronic viral hepatitis and cirrhosis. It had been reported that integrated HBV DNA could be detected both in HBsAg carriers and in anti‐hepatitis B core positive patients without HBsAg, however, IFN acts mainly as antiviral, immunomodulatory and antiproliferative agents but not as an inhibitor of integration of HBV DNA . The reasons IFN therapy improves overall survival include: (i) relieving active hepatitis and improving hepatic fibrosis and liver function; (ii) decreasing the severity of a recurrent tumor and thus be amenable to secondary curative ablation or resection; and (iii) survival gain comes in part from a significantly improved recurrence survival in patients treated with IFN (standard IFN treatment for 12 months can induce sustained off‐treatment response in patients with HBeAg positive chronic hepatitis B).…”
Section: Discussionmentioning
confidence: 99%
“…It had been reported that integrated HBV DNA could be detected both in HBsAg carriers and in anti-hepatitis B core positive patients without HBsAg, 38 however, IFN acts mainly as antiviral, immunomodulatory and antiproliferative agents but not as an inhibitor of integration of HBV DNA. 39 The reasons IFN therapy improves overall survival include: 40,41 (i) relieving active hepatitis and improving hepatic fibrosis and liver function; (ii) decreasing the severity of a recurrent tumor and thus be amenable to secondary curative ablation or resection; and (iii) survival gain comes in part from a significantly improved recurrence survival in patients treated with IFN (standard IFN treatment for 12 months can induce sustained off-treatment response in patients with HBeAg positive chronic hepatitis B). From the above, we can conclude that although IFN does not prevent recurrence in HBV-related HCC patients, it still shows long-term beneficial effects in HBV-related HCC in other ways.…”
Section: Discussionmentioning
confidence: 99%